Chinese Religions and the Cuban Revolution: A Case Study of the Guan Yu Cult - Kosec, Maja Maria (Poligrafi, 2022)
The issue of religious practices within the Chinese diaspora in Cuba is increasingly debated within Chinese studies in Latin America. As the Chinese and African diasporas in Cuba have intermingled ethnically, their religious practices have historically also intermingled. While the rise of Afro-Cuban religions in recent decades is primarily understood as a response to centuries of Spanish colonialism and perceived as a resistance to Eurocentric hegemonic power, this article aims to examine the efforts of the Chinese diaspora to re-evaluate their religions from the same decolonial perspective. This article aims to determine the tendencies of interactions between Chinese religious beliefs and Cuba’s religions before and after the Cuban Revolution, including after the fall of the socialist bloc. Specifically, it examines whether post-revolution state atheism had an impact on the religious beliefs and ethnic heritage of members of the Chinese diaspora. In the 1990s there was a revival of the Guan Yu (关羽) cult which has been often interpreted as a consequence of the economic interests of the Chinese and Afro-Chinese diaspora or as a consequence of the interests of the Cuban government. However, we must also be aware of the broader historical, social and political context at play here.